2012
DOI: 10.1371/journal.pone.0044390
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing-Based Analysis of the Microbiome Associated with the Horn Fly, Haematobia irritans

Abstract: The horn fly, Haematobia irritans, is one of the most economically important pests of cattle. Insecticides have been a major element of horn fly management programs. Growing concerns with insecticide resistance, insecticide residues on farm products, and non-availability of new generation insecticides, are serious issues for the livestock industry. Alternative horn fly control methods offer the promise to decrease the use of insecticides and reduce the amount of insecticide residues on livestock products and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 74 publications
1
28
0
1
Order By: Relevance
“…In insects, M. morganii was found in the intestines of house fly larvae (Musca domestica [Diptera: Muscidae]) (Zurek et al 2000), gastrointestinal tracts of Drosophila melanogaster (Diptera: Drosophilidae) (Cox & Gilmore 2007), adults and eggs of horn fly (Haematobia irritans [Diptera: Muscidae]) (Palavesam et al 2012), midgut of phlebotomine sand fly (Lutzomyia longipalpis [Diptera: Psychodidae]) (Gouveia et al 2008;Peterkova-Koci et al 2012), gastrointestinal tracts of the Mediterranean fruit fly (Ceratitis capitata [Diptera: Tephritidae]) (Ami et al 2009;Yuval et al 2013), in isolations made from the whole body of the guava fruit fly (Anastrepha striata [Diptera: Tephritidae]) (Martinez et al 2012), and in the gastrointestinal tracts of the oriental fruit fly (Bactrocera dorsalis [Diptera: Tephritidae]) (Pramanik et al 2014;Liu et al 2016). To our knowledge, no pathogenicity tests were conducted in any of these studies on fruit fly species, especially in regards to fruit fly larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, M. morganii was found in the intestines of house fly larvae (Musca domestica [Diptera: Muscidae]) (Zurek et al 2000), gastrointestinal tracts of Drosophila melanogaster (Diptera: Drosophilidae) (Cox & Gilmore 2007), adults and eggs of horn fly (Haematobia irritans [Diptera: Muscidae]) (Palavesam et al 2012), midgut of phlebotomine sand fly (Lutzomyia longipalpis [Diptera: Psychodidae]) (Gouveia et al 2008;Peterkova-Koci et al 2012), gastrointestinal tracts of the Mediterranean fruit fly (Ceratitis capitata [Diptera: Tephritidae]) (Ami et al 2009;Yuval et al 2013), in isolations made from the whole body of the guava fruit fly (Anastrepha striata [Diptera: Tephritidae]) (Martinez et al 2012), and in the gastrointestinal tracts of the oriental fruit fly (Bactrocera dorsalis [Diptera: Tephritidae]) (Pramanik et al 2014;Liu et al 2016). To our knowledge, no pathogenicity tests were conducted in any of these studies on fruit fly species, especially in regards to fruit fly larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an experiment by Nyirady (1973) showed that Rhodnius prolixus, also a vector of Chagas' disease, is killed when exposed to the subspecies thuringiensis. Brevibacterium avium and B. iodinum have only been reported in haematophagous arthropods and are described as a non-pathogenic bacteria with low abundance in their arthropod hosts (Hillesland et al, 2008;Valiente Moro et al, 2009;Palavesam et al, 2012). To our knowledge Delftia tsuruhatensis has not been previously reported in other arthropods, making this study the first report of its presence in an insect.…”
Section: Discussionmentioning
confidence: 74%
“…Our analysis found that out of the 13 species identified in our study, Bacillus megaterium and S. saprophyticus appear to be the most common bacterial species described in other arthropods. A variety of studies globally have described both species in insects and mites (Aksoy and Ozman-Sullivan, 2008;Hillesland et al, 2008;Rani et al, 2009;Valiente Moro et al, 2009Joyce et al, 2011;Zouache et al, 2011;Mukhopadhyay et al, 2012;Palavesam et al, 2012;Chandel et al, 2013;He et al, 2013;Tagliavia et al, 2014;Zhang et al, 2014;Maleki-Ravasan et al, 2015). Of these two species, S. saprophyticus was the bacterial species that was most reported, but had no potential phenotypic traits associated with its arthropod hosts.…”
Section: Discussionmentioning
confidence: 99%
“…However, further selection of transgenic flies to develop later generations will be helpful to this effort. It has also been reported that many bacterial species are associated with the horn fly (Palavesam et al, 2012). The mechanisms involved in gene transfer among prokaryotes and genomic integration are not fully understood (Brigulla & Wackernagel, 2010).…”
Section: Southern Blot and Germ-line Transformationmentioning
confidence: 99%